Whose landscape? - An anthropological perspective on landscape perception in reindeer tending (In Swedish with Summary in English) - Anna Järpe (Rangifer, 2005)
When we talk publicly about landscape and land use, both in legal and in popular contexts, the evaluation of our natural environment is usually based on an industrial concept of land and landscape. "Nature" is seen as a resource to be used or managed in different ways. My research originates in a questioning of this assumption: can we take for granted that the same perceptions and evaluations are shared by all concerned parties? In this article, I will use an ecologic anthropological perspective to consider the livelihood of reindeer tending and suggest an alternative to what can be called a scientific understanding of the world. I maintain that the relations that people have with their environment, and the values that they ascribe to it, are perceptions that are shaped and affected in our interactions with the surrounding world, and that these perceptions vary between different groups of people. Land use, land rights, access to fishing waters, and who gets to hunt what; these are not only questions about how we should manage the landscape, but also about whose landscape we are managing. Arguing that the reindeer tenders' landscape is a shifting mosaic of varying conditions that they must relate to rather than an object to be used and controlled by human interests, I want to show how anthropological research can provide an insight into the different perspectives and modes of understanding that we need to consider in the formulation of future policies and laws. At least if we want to resolve land use conflicts in contested areas fairly and on a sustainable long-term basis.